Abundancia, estructura poblacional y crecimiento de Atrina maura (Bivalvia: Pinnidae) en una laguna costera tropical del Pacífico mexicano - Ahumada-Sempoal, Miguel Angel (2002)
The abundance, population structure, and growth of the Pen-shell Atrina maura in the Corralero- Alotengo tropical lagoon system in Oaxaca, Mexico, were studied from February to September of 1997. An abundance analysis showed significant temporal and spatial differences (Kruskal-Wallis, p< 0.001). Two spatial groups of abundance were found in the area, one from the mouth of the lagoon system to the middle of the Penshell bank, and the other between the middle of the Pen-shell bank and the head of the system. Three temporal periods of abundance were found (February-April-May; July-August; March-June-September). The distribution of population size showed that benthic recruitment of A. maura occurred from February to July. Length frequency of A. maura is commonly wide-ranging; nevertheless, in this study Pen-shell organisms with a valve length of 15 cm were frequently found. The growth rate length was 3.7 cm/month during the dry season (February to May), and 3.5 cm/month during the rainy season (June to September). Sex ratio was maintained at 1:1 from February to May, but males were dominant from June to August, and the minimum length for reproduction was registered at 10 cm valve length.